Fortalecimento da ouvidoria do SUS a partir da Comissão Intergestores Regional – experiência na região de saúde Rio Vermelho-Goiás - Alarcao, Jonas Carlos Berquo (2014)
The SUS Ombudsman is a channel of qualified citizens hearing, capable of guaranteeing them the fundamental right to health, insofar as it presents to the system management instances, the needs or weaknesses identified by citizens or users. For the perfect operation of the SUS Ombudsman, it must be configured on network with software deployment demands management : SUS Ombudsman system. In Goiás state , till the beginning of 2014, the number of municipalities with the implanted system was extremely low. The state network is organized to the level of Regional Health, located in the municipalities of each region headquarters, with the existence of Ombudsman regional dialogues . In Rio Vermelho Health Region , we observed a number of issues regarding the Ombudsman work that were impeding the advance of the network to the municipal level. This study intended to raise awareness of the local health managers in the region, under the Inter-Regional Commission - CIR, on the role of the SUS Ombudsman and its importance and thereby to get achieving maximum response time to citizens, to institute the responsible staff for the Municipal Ombudsman Health and to deploy SUS Ombudman System in 100% of the municipalities in the region. For this, we used an Intervention Project, based on the assumptions of action research. The intervention was structured in the form of an action plan and implemented through strategies developed by the Department of Rio Vermelho Goiás Health Region in partnership with the Management of the Ombudsman, both organs of the State Office of Health. As results, we have obtained: a. pact of maximum response to ombudsman demands directed to municipalities, the setting of the responsible ones by Municipal Ombudsman in 16 municipalities in Rio Vermelho Region and the expansion of the network state Ombudsman with the implementation of SUS Ombudsman system in 15 municipalities. We have noted that in a Health Region, it is fundamental the integration of Regional Health with municipalities under their geographical jurisdiction, in particular, within the CIR space, since this integration when directed to building or strengthening the process regionalization of health always results in advances in the Regional System. Using the space of CIR to discuss the strengthening of the Ombudsman allowed us to comprehend the need for it in a network structure and to include municipalities on network. As the new structure and workflow established in the region, it will be possible to achieve new breakthroughs in the management of the Ombudsman demands such as: to reduce further the response time, to decrease the number of unanswered demands and to use the information in the management system, both in regional and municipal levels